Psychometric properties of the positive and negative affect schedule for children (PANAS-C) in Peru - Casuso, Liliana; Gargurevich, Rafael; Van den Noortgate, Wim; Van den Bergh, Omer (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2016)
This study aims at investigating the psychometric properties of The Positive and Negative Affect Schedule for Children (PANAS-C) in Peru. After translating the scale into Spanish, its validity and reliability were investigated in data collected from a two-wave longitudinal study with a sample of Peruvian preadolescent students (N = 170). The factor structure of the scale was investigated by confirmatory factor analytic techniques and the convergent and discriminant validity were explored using the Louvain Loneliness Scale for Children and Adolescents and the Stressful Events Inventory for Preadolescents. Results support the suitability of a two-factor model (Positive affect and Negative affect) in all cases. Results also showed good convergent and discriminant validity as well as good reliability. The present findings suggest that PA and NA constructs are less distinguishable in younger children and that these constructs become more clearly defined as young children grow up, possibly due to an increasing ability to categorize emotional experience.